2018
DOI: 10.1007/s00264-018-3885-z
|View full text |Cite
|
Sign up to set email alerts
|

Total ankle replacement leads to high revision rates in post-traumatic end-stage arthrosis

Abstract: Total ankle replacement in post-traumatic end-stage arthrosis patients is associated with high revision rates. High rates of symptomatic periprosthetic bone cysts caused high rates of revision surgery and worse outcomes, which were not improved by secondary TTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 17 publications
1
29
2
Order By: Relevance
“…Interestingly, if we had considered only the peak axial force during level walking as has been done by previous investigators, 5,6 the results would have been smaller peak micromotions (Table 3) and smaller amounts of bone at risk of failure (Table 4) We found that the fixation design played an important role in the magnitude of the maximum peak micromotion: the stem design had four to five times larger values (874-1125 µm) than the three spikes and keel designs, for which the peak micromotion was both smaller and similar to one another (~54-140 µm). Moreover, the distribution of micromotion at the instant of the maximum peak micromotion was also dependent on the fixation design: for the three spikes design, the highest micromotion was located posteriorly; for the keel, the highest micromotion was located anteriorly; and the stem design showed a concentric pattern around the stem.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, if we had considered only the peak axial force during level walking as has been done by previous investigators, 5,6 the results would have been smaller peak micromotions (Table 3) and smaller amounts of bone at risk of failure (Table 4) We found that the fixation design played an important role in the magnitude of the maximum peak micromotion: the stem design had four to five times larger values (874-1125 µm) than the three spikes and keel designs, for which the peak micromotion was both smaller and similar to one another (~54-140 µm). Moreover, the distribution of micromotion at the instant of the maximum peak micromotion was also dependent on the fixation design: for the three spikes design, the highest micromotion was located posteriorly; for the keel, the highest micromotion was located anteriorly; and the stem design showed a concentric pattern around the stem.…”
Section: Resultsmentioning
confidence: 99%
“…3 To ensure both adequate micromotion and successful load transfer, TAA designs have incorporated supplemental fixation features, such as keels, stems, or spikes ( Figure 1). Despite these design efforts, reported revision rates range from 5% in 2 years 4 to 42% in 5 years, 5 with the leading causes for failure being periprosthetic osteolysis, component loosening, and subsidence. [4][5][6] These failure modes are thought to be related to the mechanics of the interaction between the implant and the bone.…”
mentioning
confidence: 99%
“…Although the ankle joint mobility is retained, the lifetime of the prosthesis is shorter. Total ankle arthroplasty is characterized by a high failure rate; in fact, the overhaul rate is as high as 32.9%-42% 10,11 . With recent progress in the research on ankle joint biomechanics, prosthesis design, and simulation technology, the clinical outcomes of total ankle replacement are now adequate for the early and middle stages of the disease 12 .…”
Section: Introductionmentioning
confidence: 99%
“…According to Hurowitz and colleagues, 16 there was a 10% failure rate at the first year for the agility total ankle replacement, and this rate rose to over 30% in the next year. Gramlich et al 12 also reported a high revision rate and unsatisfactory outcomes after total ankle replacement for end-stage posttraumatic arthritis. A recent meta-analysis demonstrated a higher overall complication rate after ankle arthrodesis, but a higher revision rate after total ankle arthroplasty.…”
Section: Discussionmentioning
confidence: 99%